2003
DOI: 10.1530/eje.0.1490145
|View full text |Cite
|
Sign up to set email alerts
|

The associations of age, lifestyle factors and chronic disease with testosterone in men: the Tromso Study

Abstract: Objective: To study whether lifestyle factors and/or chronic disease are associated with the age-related decline of total and free testosterone in men, or if these factors might be associated with the variation of total and free testosterone but not with their age-related decline. Design: A population-based, cross-sectional study was used. Methods: Total testosterone and sex hormone binding globulin (SHBG) levels were analyzed and free testosterone levels were calculated in 1563 men participating in the Tromsø… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
198
6
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(249 citation statements)
references
References 38 publications
43
198
6
2
Order By: Relevance
“…Higher BMI and waist circumference are associated with lower total, bioavailable or free testosterone and SHBG. 6,7,[144][145][146] The association between higher BMI and lower total testosterone appears more consistent that between BMI and free testosterone. 146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 76%
See 2 more Smart Citations
“…Higher BMI and waist circumference are associated with lower total, bioavailable or free testosterone and SHBG. 6,7,[144][145][146] The association between higher BMI and lower total testosterone appears more consistent that between BMI and free testosterone. 146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 76%
“…146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels. 6,7,147 However, other studies have not confirmed these associations. 148,149 It is important to note the severe damaging effects of smoking on cardiovascular and respiratory health far outweigh any possible benefit it may confer on testosterone levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 96%
See 1 more Smart Citation
“…As early as 50-60 years ago it was realized that aging is accompanied by significant reduction in testosterone levels [97,98]. Although some follow-up studies failed to detect age-related decline in plasma testosterone levels in older men [99][100][101][102][103][104], subsequent population-based cross-sectional and longitudinal studies have confirmed progressive loss of testosterone with aging in healthy men [96,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Mirroring this decline in plasma testosterone concentration is an age associated increase in sex-hormonebinding globulin (SHBG) level [117], a major plasma carrier of testosterone, resulting in even more dramatic decreases in unbound free testosterone [110,[123][124][125], and weakly bound bioavailable testosterone [126,127].…”
Section: Humansmentioning
confidence: 99%
“…161 However, many studies have evaluated the effect of cigarette smoking on levels of male reproductive hormones, and findings still remain controversial. [161][162][163][164] Coffee consumption and physical exercise increased levels of TT and SHBG. 154,160 Interestingly, with the aim to determine whether greater participation in healthier behaviors, (i.e., refraining from smoking, maintaining physical activity, avoiding excessive alcohol consumption, eating more fish and less meat, avoiding adding salt to food, having a BMI] < 25 kg/m 2 , and consuming reduced-fat milk or skimmed milk) predicted reduced risk of subsequent lower circulating T in older men, Yeap et al conducted a crosssectional analysis of a population-based follow-up study concerning 3,453 men aged 65-83 years.…”
mentioning
confidence: 99%